AVAILABILITY AND AFFORDABILITY OF ESSENTIAL MEDICINES: EXPLORING THE HEALTH SEEKING BEHAVIOURS AND HEALTH SERVICE UTILISATION FOR CHILDREN UNDER-5 YEARS LIVING IN SQUATTER SETTLEMENT OF KARACHI, PAKISTAN - Shafiq, Yasir; Shaikh, Babar Tasneem; Kumar, Ramesh (Journal of Ayub Medical College Abbottabad, 2011)
Background: Child health outcomes in the poor communities are largely affected by the nonavailability of essential medicines at government health facilities and non-affordability of prescribed medicines at private retail pharmacies. This phenomenon largely defines health seeking behaviours and health service utilisation patterns of the families of the children. Methods: Using observational visits, we examined the shelf-availability of medicines for children less than 5 years of age at a rural health centre and conducted focus group discussions with the mothers to explore the effects of nonavailability and non-affordability of medicines. We also validated all information by interviewing the health care providers of the area. Results: We found that erratic and insufficient supply of essential medicines at the government health facility and a limited purchasing power to buy medicines from a retail pharmacy, led to considerable '˜financial burden' on the poor people, non-compliance with the treatment, health care seeking from informal health providers and healer shopping. This trend has a serious repercussion on the health seeking behaviours and of course the health outcomes, especially among children. Conclusion: On the users' side, health education and health promotion campaign must be instituted to explain the adverse effects on child health ensure appropriate health care seeking behaviours. For the supply side, the health care authorities must ensure the availability of essential medicines for the children at the government facilities. Local community representatives must be involved in the matters related to medicines stock management at the facility. Keywords: Essential Medicines, Health Seeking Behaviours, Health Service Utilization, Child Health, Developing Countries, Healthcare System